Generation of V2a Interneurons from Mouse Embryonic Stem Cells - Brown, Chelsea R. (Mary Ann Liebert, Inc., 2014)
V2a interneurons of the ventral spinal cord and hindbrain play an important role in the central pattern generators (CPGs) involved in locomotion, skilled reaching, and respiration. However, sources of V2a interneurons for in vitro studies are limited. In this study, we developed a differentiation protocol for V2a interneurons from mouse embryonic stem cells (mESCs). Cells were induced in a 2(−)/4(+) induction protocol with varying concentrations of retinoic acid (RA) and the mild sonic hedgehog (Shh) agonist purmorphamine (Pur) in order to increase the expression of V2a interneuron transcription factors (eg, Chx10). Notch signaling, which influences the commitment of p2 progenitor cells to V2a or V2b interneurons, was inhibited in cell cultures to increase the percentage of V2a interneurons. At the end of the induction period, cell commitment was assessed using quantitative real-time polymerase chain reaction, immunocytochemistry, and flow cytometry to quantify expression of transcription factors specific to V2a interneurons and the adjacent ventral spinal cord regions. Low concentrations of RA and high concentrations of Pur led to greater expression of transcription factors specific for V2a interneurons. Notch inhibition favored V2a interneuron over V2b interneuron differentiation. The protocol established in this study can be used to further elucidate the pathways involved in V2a interneuron differentiation and help produce sources of V2a interneurons for developmental neurobiology, electrophysiology, and transplantation studies.